Prebiotic Activity of Ambon Banana (Musa acuminata (AAA Group) ‘Ambon’) Peel Starch Against Lactobacillus. acidophilus and Escherichia coli In Vitro - Rusdi, Bertha; Yuniarni, Umi (FITOFARMAKA: JURNAL ILMIAH FARMASI, 2023)
Prebiotics are compounds with the ability to specifically enhance the population of advantageous bacteria in the gastrointestinal tract. Starch is a polysaccharide which has prebiotic activity. Agricultural waste like banana peel contains prebiotic polysaccharides including starch. The prebiotic effect of starch from many varieties of banana peel has been explored by researchers. Although Ambon banana is a variety that is commonly consumed in Indonesia, the prebiotic activity of its peel, particularly the peel starch,  has not been studied yet. Thus, this study aims to research the prebiotic activity of Ambon banana peel starch against probiotic bacteria of the Lactobacillus acidophilus and the opportunistic pathogen bacteria of Eschericia coli. In this research, starch was extracted from banana peel (var. pisang Ambon) and prebiotic activity of the starch was tested on L. acidophilus and E. coli.  The number of bacteria was calculated at 0 and 24 hours of incubation using plate count methods.The result showed that at the concentration of 1% w/v, Ambon banana peel starch increases the number of L. acidophilus while inhibiting the growth of E. coli. The L. acidophilus culture in the starch-containing media had SCFAs (acetic, butyric and propionic acid) that were  known to have good impact to human health.